(untitled) (Interdisciplinary Studies Journal, 2026)
The availability of pornographic content on the internet has intensified debates about its effects on the formation of expectations, beliefs, and sexual practices among young adults. This study analyzed how pornography consumption influences perceptions, fantasies, and sexual behaviors of male university students. This qualitative, descriptive, and exploratory study employed a questionnaire administered to 100 sexually active male university students from the Federal District, Brazil. The results indicated that, although pornography expands imaginative repertoires, most participants differentiate fantasy and practice, not seeking to directly reproduce the scenes consumed. Comparisons of body image and sexual performance with pornographic actors were reported, with impacts on self-esteem and sexual confidence. Variations in sexual interest within stable relationships also emerged, attributed to discrepancies between everyday sexuality and pornographic performativity. Regarding risk behaviors, pornography consumption did not determine condom use; however, some participants associated more impulsive content with momentarily less cautious decisions. It is concluded that pornography consumption exerts a multifaceted influence on male sexual experience, being perceived both as an exploratory resource and as potentially harmful when associated with unrealistic expectations, reinforcing the importance of educational approaches that promote critical reflection and a realistic understanding of affective-sexual relationships.